Common Backswimmer Notonecta glauca (Linnaeus 1758) (Hemiptera: Notonectidae) - Taryn B. Griffith; Jennifer L. Gillett-Kaufman (EDIS, 2021)
Notonecta glauca, the common backswimmer, is an aquatic insect most easily recognizable by their long hind legs. Insects in the family Notonectidae are commonly referred to as backswimmers or greater water boatman. They propel themselves through the water on their dorsal side with their abdomen facing upwards, this is how they acquired their common name. Insects commonly referred to as lesser water boatman are in the family Corixidae, not Notonectidae, like common backswimmers. They can inflict wounds to humans with their proboscis (mouthpart), but this is very rare and often is a result of rough handling.